Frailty and depressive symptoms in older kidney transplant recipients: opportunities for collaboration between transplant nephrologists and geriatricians - Vankova, Hana; Schmalz, Michal; Andel, Ross; Rajnochova Bloudickova, Silvie (BMC geriatrics, 2024)
BACKGROUND: Frailty is one of the key syndromes in geriatric medicine and an important factor for post-transplant outcomes. We aimed to describe the prevalence of frailty and examine the correlates of frailty and depressive symptoms in older kidney transplant recipients (KTRs). METHODS: This cross-sectional study involved 112 kidney transplant recipients (KTRs) aged 70 and above. Frailty syndrome was assessed using the Fried frailty criteria, and patients were categorized as frail, pre-frail, or non-frail based on five frailty components: muscle weakness, slow walking speed, low physical activity, self-reported exhaustion, and unintentional weight loss. Depressive symptoms were measured using the 15-item Geriatric Depression Scale (GDS). The relationship between frailty and depressive symptoms was evaluated using multinomial logistic regression, with the three frailty categories as the dependent variable and the severity of depressive symptoms as the independent variable, while controlling for age, gender, renal graft function, and time since transplant surgery. RESULTS: The participants had a mean age of 73.3 ± 3.3 years, and 49% were female. The prevalence of frailty syndrome was 25% (n = 28), pre-frailty was 46% (n = 52), and 29% (n = 32) of the KTRs were non-frail. The mean score for depressive symptoms was 3.1 ± 2.4 points, with 18% scoring above the clinical depression cutoff. Depressive symptoms were positively correlated with frailty (r = .46, p < .001). Among the frailty components, self-reported exhaustion (r = .43, p < .001), slow walking speed (r = .26, p < .01), and low physical activity (r = .44, p < .001) were significantly positively correlated with depressive symptoms, while muscle strength (p = .068) and unintentional weight loss (p = .050) were not. A multinomial logistic regression adjusted for covariates indicated that, compared to being non-frail, each additional point on the GDS increased the odds of being pre-frail by 39% (odds ratio [OR] = 1.39, 95% confidence interval [CI] 1.01-1.96) and roughly doubled the odds of being frail (OR = 2.01, 95% CI 1.39-2.89). CONCLUSION: There is a strong association between frailty and depression in KTRs aged 70 years and older. Targeted detection has opened up a new avenue for collaboration between geriatricians and transplant nephrologists.
Keywords: křehkost; Female; Prevalence; nefrologové; Geriatric Assessment; ženské pohlaví; průřezové studie; geriatrie; Geriatrics; lidé; Transplant Recipients; geriatrické hodnocení; Aged, 80 and over; Frail Elderly; transplantace ledvin; prevalence; příjemce transplantátu; Cross-Sectional Studies; Kidney Transplantation; Male; křehký senior; Aged; Frailty; Nephrologists; deprese; senioři nad 80 let; senioři; mužské pohlaví; Depression; Humans